2016
DOI: 10.1016/j.fertnstert.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the use of elective single-embryo transfer and pregnancy outcomes in the United States, 2004–2012

Abstract: Objective To evaluate factors associated with elective single embryo transfer (eSET) utilization and its effect on assisted reproductive technology (ART) outcomes in the United States. Design Historical cohort Setting Not applicable Patient(s) Fresh IVF cycles of women 18–37 years using autologous oocytes with either one (SET) or two (DET) embryos transferred and reported to the Society for Assisted Reproductive Technology Clinic Outcome Reporting System between 2004 and 2012. Cycles were categorized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…The recommendation to use eSET in the United States has been inconsistently implemented, likely owing to an absence of financial subsidies for IVF, as well as patient and provider perceptions of reduced LBR (21)(22)(23). Analyses of national data in 2004-2012 have shown that eSET is more likely to occur in cases with insurance coverage, retrieval of R16 oocytes, and the transfer of blastocyst embryos (24). Application of a validated prediction model based on 2006-2012 national data demonstrated that the cumulative LBR is as good as or better with eSET over the course of one fresh and one frozen cycle than with double embryo transfer (DET) in a single cycle, while reducing the MBR by more than tenfold (25).…”
mentioning
confidence: 99%
“…The recommendation to use eSET in the United States has been inconsistently implemented, likely owing to an absence of financial subsidies for IVF, as well as patient and provider perceptions of reduced LBR (21)(22)(23). Analyses of national data in 2004-2012 have shown that eSET is more likely to occur in cases with insurance coverage, retrieval of R16 oocytes, and the transfer of blastocyst embryos (24). Application of a validated prediction model based on 2006-2012 national data demonstrated that the cumulative LBR is as good as or better with eSET over the course of one fresh and one frozen cycle than with double embryo transfer (DET) in a single cycle, while reducing the MBR by more than tenfold (25).…”
mentioning
confidence: 99%
“…In countries or regions where state funded or supported fertility treatment exists, the rates of single embryo transfer are far higher. The factor most influencing the likelihood a patient will undergo a single embryo transfer over a double or greater number embryo transfer is whether or not they have health insurance, a greater influencing factor than that of maternal age [33]. In Australia where fertility treatment is subsidised by the state and rates of health insurance are high, the rate of single embryo transfer is over 75% and reflected in the multiple pregnancy rate from IVF being below 6% [34].…”
Section: In-vitro Fertilisationmentioning
confidence: 99%
“…Twin gestation also compound the health threats to women with advanced age, who have a three-time higher risk of pregnancy-related mortality than do younger counterparts (MacKay, Berg & Atrash, 2001). Ideally, the goal of ART is to achieve a singleton gestation (Styer et al, 2016;Thurin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%